2019
DOI: 10.1016/j.ymssp.2019.03.048
|View full text |Cite
|
Sign up to set email alerts
|

A Gaussian process latent force model for joint input-state estimation in linear structural systems

Abstract: The problem of combined state and input estimation of linear structural systems based on measured responses and a priori knowledge of structural model is considered. A novel methodology using Gaussian process latent force models is proposed to tackle the problem in a stochastic setting. Gaussian process latent force models (GPLFMs) are hybrid models that combine differential equations representing a physical system with data-driven non-parametric Gaussian process models. In this work, the unknown input forces … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 40 publications
(48 reference statements)
0
34
0
Order By: Relevance
“…One of the most useful aspects of this approach is that the whole system remains a linear Gaussian state-space model which can be solved with the Kalman filter and RTS smoother to recover the filtering and smoothing distributions exactly. It is this form of the model that has been exploited previously in structural dynamics [5,6,10].…”
Section: Input Estimation As a Latent Force Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most useful aspects of this approach is that the whole system remains a linear Gaussian state-space model which can be solved with the Kalman filter and RTS smoother to recover the filtering and smoothing distributions exactly. It is this form of the model that has been exploited previously in structural dynamics [5,6,10].…”
Section: Input Estimation As a Latent Force Problemmentioning
confidence: 99%
“…Some examples include, Naets et al [2] who use a Kalman filter approach for force identification, the Dual Kalman Filter approach of Azam et al [3], and Maes et al [4] who show the benefit of a smoothing approach to the problem at hand. Nayek et al [5] adopt a Gaussian process latent force approach to the joint input-state problem, in a similar manner to the work of Rogers et al [6] who also include parameter estimation.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we are only interested in supervised learning techniques. Popular supervised learning techniques include Gaussian process or Kriging [19][20][21][22], Polynomial chaos expansion (PCE) [23][24][25], analysis-of-variance decomposition [26][27][28][29], Polynomial chaos based Kriging (PC-Kriging) [30][31][32][33] etc. In this work, we review three machine learning techniques in the context of stochastic low-velocity impact analysis.…”
Section: R E V I S E D P R O O Fmentioning
confidence: 99%
“…The authors of this paper have previously introduced the use of this model for joint input-state-parameter estimation for structural dynamical systems in [20], where the method is demonstrated on a single-degree-of-freedom system and the mass of the system is considered known. Independently of this, Nayek et al [21] have recently shown the usefulness of this method in the case of input-state estimation only, i.e. the parameters of the system are considered known.…”
Section: Introductionmentioning
confidence: 99%